PENGARUH PROFITABILITY, LEVERAGE, DAN FIRM SIZE TERHADAP TAX AVOIDANCE - Yusiana, Emilia; Yuniarwati, Yuniarwati (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to analyze the effect of profitability, leverage, and firm size towards tax avoidance on manufacturing companies listed in Indonesian Stock Exchange (IDX) 2018-2020 period. Secondary data in the form of financial statementobtained from website idx.co.id was used in this study. This study used 70 manufacturing companies that have been previously selected by purposive sampling technique with total of 210 data for 3 (three) years. Data in this study were processed with Eviews 12. The result of this study indicates that leverage has positive and significant effect towards tax avoidance, however profitability and firm size have no significant effect towards tax avoidance.